Cure for tantrums? Longitudinal associations between parental digital emotion regulation and children's self-regulatory skills - Konok, V.; Binet, M.-A.; Korom, Á.; Pogány, Á.; Miklósi, Á.; Fitzpatrick, C. (Frontiers in Child and Adolescent Psychiatry, 2024)
Parents often use digital devices to regulate their children's negative emotions, e.g., to stop tantrums. However, this could hinder child development of self-regulatory skills. The objective of the study was to observe bidirectional longitudinal associations between parents' reliance on digital devices to regulate their child's emotions and self-regulatory tendencies (anger/ frustration management, effortful control, impulsivity). Parents (N=265) filled out the Child Behavior Questionnaire -Short Form and the Media Assessment Questionnaire twice: the initial assessment (T1) took place in 2020 (mean child age = 3.5 years old), and follow-up (T2) occurred a year later in 2021 (mean child age = 4.5 years old). Higher occurrence of parental digital emotion regulation (PDER) in T1 predicts higher anger and lower effortful control in T2, but not impulsivity. Higher anger in T1, but not impulsivity and effortful control, predicts higher PDER in T2. Our results suggest that parents of children with greater temperament-based anger use digital devices to regulate the child's emotions (e.g., anger). However, this strategy hinders development of self-regulatory skills, leading to poorer effortful control and anger management in the child.